PENGARUH PERUBAHAN TR TERHADAP NILAI CNR DAN EFISIENSI KONTRAS PADA CITRA MRI HEAD SEQUENCE T1 WEIGHTED IMAGE - Syamsul Hidayah; Heri Sutanto; Rudi Sohidi Tohir (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
MRI sequence difference produces different images. Sequence T1 weighted image (T1WI) uses to assess the anatomical image. To produce TI Weighted Image needs low TE ( time Echo) lower than 50 ms and low TR (Time Repetition) lower than 1500 ms. To produce a good image needs high contrast in order to differentiate tissues was examined. The purpose of this research is to know CNR maximum and contrast efficiency that accepted.CNR value was obtained by measuring SNR white matter and gray matter for every image MRI Head T1WI with TR variation. The TR was used is 100 ms until 1500 ms with range 100 ms every image. Contrast efficiency value obtained by dividing the value of CNR with the square root of the scan time. The CNR maximum value that has been obtained from this research is 40,55 in TR 800 ms. While contrast efficiency value that has been obtained is 2,57 in TR 600 ms. Keywords: MRI, T1 Weighted Image, CNR optimum, contrast efficiency